Description of a new species of the genus Neotrops from Colombia (Araneae: Oonopidae) - Izquierdo, Matías Andres (2014)
A new species of the genus Neotrops (Araneae: Oonopidae) from Colombia, N. ramirezi, is described on the basis of male and female specimens collected in Yotoco Natural Reserve (Valle de Cauca). It is the third species of the genus reported for the country.